2013
DOI: 10.1142/s0218194013500216
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of an Editor/Interpreter for a Visual Logic Programming Language

Abstract: The design and implementation of a programming environment including an editor, a debugger and an interpreter engine for Lograph, a general-purpose visual logic programming language, is discussed. The rationale for user-interface design decisions is presented, the goal of which is to increase cognitive support for the creation, exploration and debugging of Lograph programs. The design of the interpreter engine allows for animation of execution in the debugger. The engine takes full advantage of an efficient im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The experimental results showed that the designed interpreter had high efficiency and stability in interpreting the robot program and met the operational requirements of industrial robots. ▪ [11] designed and implemented a programming environment including an editor, a debugger, and an interpreter engine for Lograph, a general-purpose visual logic programming language. The engine takes full advantage of an efficient implementation of Prolog and operates on a Prolog translation of Lograph programs and queries.…”
Section: Related Workmentioning
confidence: 99%
“…The experimental results showed that the designed interpreter had high efficiency and stability in interpreting the robot program and met the operational requirements of industrial robots. ▪ [11] designed and implemented a programming environment including an editor, a debugger, and an interpreter engine for Lograph, a general-purpose visual logic programming language. The engine takes full advantage of an efficient implementation of Prolog and operates on a Prolog translation of Lograph programs and queries.…”
Section: Related Workmentioning
confidence: 99%
“…The design and implementation of a Lograph interpreter with support for animated and single step execution of queries was discussed in [1]. Here, we report on another aspect of the programming environment, presenting the automatic layout algorithm currently used in the Lograph debugger.…”
Section: Introductionmentioning
confidence: 99%